Evaluation of Heart Rate Variabilty After Cerebral Injury in ICU Patients - Daniel da Silva Areias (2020)
Introduction: Autonomic dysfunction affecting internal homeostasis, namely cardiovascular control is a frequent phenomenon after acute brain injury. The inclusion of orthostatic training with the tilt table in the rehabilitation protocols of these patients, may improve cerebral autoregulation and induce faster recovery of sensorimotor, balance and autonomic systems. Purpose: Preliminary pilot study to describe the systemic and cerebral physiological adaptation of critically ill patients with acute brain injury submitted to orthostatism using the tilt table. Methods: Rehabilitation with orthostatism was applied to patients recovering from acute brain injury admitted in a Neurocritical care unit (NCCU). The orthostatic trial was achieved according to the tilt table protocol: the body position was gradually elevated from 0º to 60º. For each slope degree 0º, 15º, 30º, 45º and 60º, the patient stayed in the same position for 15 minutes. The trial was concluded by gradually lower the slope every 5 min for 15º until the 0º position was reached. During the procedure we continuously recorded arterial blood pressure, electrocardiogram (ECG), heart rate and cerebral oximetry with near-infrared spectroscopy (NIRS). We made offline analysis of cerebrovascular reactivity index using cerebral oximetry (COx), heart rate variability in frequency domain and baroreflex. Data recording and processing was performed using ICM+ software ® developed at Cambridge University. Results: We studied 7 patients (mean age 58) with acute brain injury (3 Traumatic Brain Injury, 3 Intracerebral Haemorrhage and 1 Acute Hydrocephalus). The median Glasgow Coma Scale (GCS) was 11(1), the mean Simplified Acute Physiology Score (SAPSII) was 31±23, the mean length of stay in NCCU and hospital was 67±26 and 107±26, respectively. In supine position, baroreflex sensitivity (BRS) and heart rate variability (HRV) total power was decreased. Low-frequency (LF) and high-frequency (HF) components of HRV were decreased and HRV LF/HF ratio was increased. Cerebral autoregulation, expressed by COx, remained mostly under 0.3 during orthostatism. During tilt test only Heart Rate demonstrated an increase with statistical significance from 15º to 45º and 60º (83 vs 94, p=0.037) and (83 vs 95, p=0.037). No other statistical difference was identified during orthostatism. Conclusion: The results of this pilot study in acute brain injury patients submitted to orthostatism challenge demonstrate that it is feasible to apply the tilt table in an acute care setting. The increase of HRV LF/HF and decrease of BRS suggest sympathetic predominance supporting autonomic nervous system impairment. The clinical relevance of online monitoring of cerebral autoregulation with COx during the tilt test warrants further evaluation.